Deliberative Democracy and Systemic Racism. Issue 1 (March 2023) - Drake, Anna
Abstract: Examining recent developments in deliberative democracy alongside growing attention to system-wide racism, I look at the ways deliberative systems theory and practice deals with the tension between the theory's normative claims and the structural injustice against which deliberative systems unfold. I focus on work aimed at deepening inclusion in deliberative systems, noting that this focus on inclusion into unjust systems stops the deliberative literature from taking full responsibility for structural and systemic racism. Taking a critical approach to the deliberative literature's capacity to confront systemic racism and live up to its normative principles of treating all people as equals, I argue that we need to reframe power to centre the relationship between race and democracy. As I do so, I propose ways to begin dismantling foundational injustice in deliberative systems, centring foundational inequalities in deliberative theory and design, and setting out differential responsibilities for listening as deliberative theorists confront the problem of white supremacy in deliberative systems.